DESIGN OF THE TAJUR KAHURIPAN TOURISM VILLAGE IN PURWAKARTA DISTRICT, WEST JAVA PROVINCE WITH THE INSPIRATION SUNDANESE TRADITIONAL OF ARCHITECTURE - NURYANTO, NURYANTO NURYANTO; Surasetja, Irawan; Ahdiat, Dadang (Journal of Architectural Research and Education, 2020)
Abstract – Research PPKBK 2014 (phase II) as acontinuation of the previous. The research focus is the planning and design of the tourism village of Kampung Tajur Kahuripan. This research into the link between the desire of the Government of Purwakarta Regency Village Tajur Kahuripan plans to develop into a tourist village in West Java support the Visit Year and Visit Indonesia Year 2014-2015. This research aims to make the planning and design of the tourist village based Sundanese Traditional of Architecture. Research sites in Kampung Tajur Kahuripan Bojong District of Purwakarta. Research method using descriptive-qualitative approach, by observing and exploring the potential of Kampung Tajur Kahuripan and communities to provide inputin the planning and designing tourist village. These results have two important formulas, namely: (1) Planning tourist village which includes: master plan, site plan which involves a series of provision of facilities for tourists, development potential, zoning functions, as well as reforestation; (2) The design of the tourist village which include: the design of the building occupants and visitors typology based on Sundanese Traditional of Architecture, such as: imah panggung, leuit, saung lisung, bale sarwaguna, homestay, and so forth. The shape of the roof of the building which includes: julang ngapak, jolopong, capit gunting, sontog, badak heuay, and tagog anjing. The concept of planning and design of Village Tourism of Tajur Kahuripan with the inspiration Sundanese Traditional of Architectural. Social and cultural life of the community is an important factoras an attraction for tourists, such as: the process of working the fields, the attitude of mutual cooperation, protecting the environment, tolerance between people, traditional arts, as well as atraditional ceremonies implementation life cycle. Keywords – tourism village, inspiration, planning-design, attraction, facilities